The Incidence Rate of Esophageal Cancer in Saudi Arabia: An Observational and a Descriptive Epidemiological Analyses - Almatroudi, Ahmad (Frontiers in Public Health, 2022)
Introduction: Esophageal cancer is the sixth most diagnosed cancer and the morality incidence of this disease is rapidly growing worldwide. A retrospective observational population based epidemiological study of esophageal cancer has been conducted and data is based on National Health Information Centre Saudi cancer registry from the period 2006-2016. The study described the age-standardized incidence rates (ASIRs) and crude incidence rates (CIRs) of esophageal cancer based on age-groups, diagnosis year and administrative areas in the Saudi Arabia populations to examine the esophageal cancer distribution and trends in Saudi Arabia. Method: For statistical assessment of data, sex ratio, t-test, Kruskal Wallis and descriptive statistics was performed using SPSS version 20.0 (IBM Corporation, Armonk, NY, USA). A total of 755 and 597 cases of esophageal cancer in males and females respectively, were reported from 2006 to 2016 in Saudi Arabia. Results: Out of all esophageal cases, highest number of cases were observed in the age group < 75 years amongst both males and females whereas the lowest percentage and mean number of esophageal cancer cases among males and females were reported in the younger age groups between 0-29 years. Within the geographical region Tabuk and Qassim regions recorded highest mean CIR and ASIR among males. In the Northern region of Saudi Arabia, the maximum CIR and ASIR sex ratio was observed whereas minimum mean CIR and ASIR were reported in Jouf and Jazan regions respectively among males. Madinah and Tabuk regions had the maximum mean CIR and ASIR respectively among females for esophageal cancer. The Northern region recorded minimum mean CIR and ASIR among females. Conclusion: The maximum substantial changes of ASIRs for esophageal cancer in males and in females from years 2006-2016 were found in Tabuk region, while the Jazan and Northern region exhibited least substantial changes of ASIRs in males and females respectively.